A Juridical Study on the Transfer of Land Rights for Afwezigheid - Dinda Keumala; Setiyono; Khairani Bakri; Anda Setiawati; Aghna Zarra Amani (Jurnal Kajian Pembaruan Hukum, 2026)
The transfer of land rights in Indonesia is fundamentally grounded in the principles of legal certainty and justice within the national agrarian system. However, legal complexities arise when the rightful landowner is in a state of afwezigheid (absence), a situation in which the legal subject's absence creates vulnerabilities in the validity and registration of land transfers. The research problems in this study are the procedures for transferring rights to land and/or buildings for people whose whereabouts are unknown (afwezigheid), and the legal considerations regarding the institution for determining a person's absence according to the Civil Code for land registration purposes, in accordance with the principles of justice and legal certainty. This research employs a normative juridical method with a qualitative approach, analysing statutory regulations, legal doctrines, and court decisions related to land transfers involving absentee owners. The study examines procedures for transferring land rights under conditions of absence, the role of judicial determinations as a substitute for the deed issued by the Land Deed Official (PPAT), and the supervisory function of courts in safeguarding the rights of absentee owners. Findings indicate that Indonesian courts play a pivotal role in balancing the principles of justice and legal certainty by validating materially lawful transactions conducted in good faith and providing a juridical basis for land registration when formal requirements cannot be fulfilled due to absence. The study concludes that judicial decisions function as an essential corrective mechanism within the land administration system. Strengthening regulatory clarity regarding afwezigheid in land transfers is necessary to enhance coherence, fairness, and sustainability in Indonesia’s land law framework.